Russian-Japanese fisheries relations and salmon issues in the Russian Far East - A. N. Makoedov; A. A. Makoedov (Известия ТИНРО)
History of the Russian-Japanese cooperation in fisheries in the Far East dem- onstrates a dynamic interaction of economic, technological and geopolitical factors. Formerly Japan, possessing technological superiority, dominated in exploitation of pacific salmon that was noted in the St. Petersburg treaty in 1875 and Portsmouth treaty in 1905. Japan leaded in modernization of fishing gears and techniques, including introduction of fixed seines and drift nets, as well as in development of fish processing technology and biological studies of pacific salmon. In the Soviet period, the national state control over resources increased, but the concessions in 1920–1930s still were dependent on Japanese capital. Until the middle of the 20th century, the salmon of Russian origin dominated in annual catch of Japan (up to 86 %). The offshore drift-net fishing played a significant role before the ban in 2015. Modern stage in salmon fishery in the Far East is distinguished by reduction of Japanese input (2–3 % or less of the total annual catch after 2006) and increasing Russian sovereignty, including restriction on drift-net fishing and implementation of regulated quotas. However, Japan continues to lead in development of salmon farming. Russia joined to the artificial reproduction of pacific salmon and established a net of fish hatcheries in Sakhalin and Kuril Islands, although their effectiveness is controversial, in particular after lowering of the juveniles return to 1 % in 2020s. The study highlights contradictions between growing investments in aquaculture and more complicated dynamics of natural populations, as well as the need for a balance between economic efficiency and environmental sustainability. The historical analysis reveals a key role of international cooperation in shaping the resource policy: from technological borrowing to scientific collaboration. Prospects of salmon farming are related on development and integration of historical experience, deep knowledge on population biology, and adaptive management that ensure long-term conservation of biological resources in changing nature and political realities.